Studi Interaksi Materi Elektron Al2O3 dengan Simulasi Monte Carlo dan wet-STEM Electron Tomography - Rahmat Firman Septiyanto; Isriyanti Affifah (Akta Kimia Indonesia, 2021)
Materials science and biology are both fields that require a three-dimensional (3D) structure characterization method. Tomography is an efficient tool for analyzing the three-dimensional structure of a material. The principle is based on the acquisition of a series of projected images at different tilt angles, and on the calculation of the three-dimensional (3D) volume reconstruction (tomogram) using a special algorithm. Various studies have been developed to perform electron tomography in Environmental Scanning Electron Microscopy (ESEM), which provides access to the observation of hydrated samples in an aquatic environment. In this study we present the feasibility of tomography on wet materials, namely Al2O3 compounds by simulating electron material interactions. From these simulations, we determine the optimum detectable thickness of water in the wet material which is calculated by Monte Carlo simulation.Keyword : Al2O3, Tomography, Monte Carlo Simulation, wet-STEM